Hormesis: a fundamental concept in biology - Edward J. Calabrese (Microbial Cell, 2014)
This paper assesses the hormesis dose response concept, including its historical foundations, frequency, generality, quantitative features, mechanistic basis and biomedical, pharmaceutical and environmental health implications. The hormetic dose response is highly generalizable, being independent of biology model (i.e. common from plants to humans), level of biological organization (i.e. cell, organ and organism), endpoint, inducing agent and mechanism, providing the first general and quantitative description of plasticity. The hormetic dose response describes the limits to which integrative endpoints (e.g. cell proliferation, cell migration, growth patterns, tissue repair, aging processes, complex behaviors such as anxiety, learning, memory, and stress, preconditioning responses, and numerous adaptive responses) can be modulated (i.e., enhanced or diminished) by pharmaceutical, chemical and physical means. Thus, the hormesis concept is a fundamental concept in biology with a wide range of biological implications and biomedical applications.